2019
DOI: 10.3390/nano9071025
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Environmental Conditions on the Fusion of Cationic Liposomes with Living Mammalian Cells

Abstract: Lipid-based nanoparticles, also called vesicles or liposomes, can be used as carriers for drugs or many types of biological macromolecules, including DNA and proteins. Efficiency and speed of cargo delivery are especially high for carrier vesicles that fuse with the cellular plasma membrane. This occurs for lipid mixture containing equal amounts of the cationic lipid DOTAP and a neutral lipid with an additional few percents of an aromatic substance. The fusion ability of such particles depends on lipid composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 50 publications
(64 reference statements)
1
20
0
Order By: Relevance
“…Applying this method, NA/NR complexes served as cargo and FLs as delivery vehicles. As already clearly shown for FLs in the absence of NR molecules and NAs [34,55], parallel experiments on NA/NR/FL complexes also proved fusion-based transfer and high biocompatibility [38]. Underlying liposomes (there named Fuse-It-mRNA) had the identical composition as characterized here as optimum (DOPE/DOTAP/DiR 1/1/0.1) and were unaffected in effectiveness by various endosomal uptake blockers while keeping natural cell functions of various cell types completely unaffected.…”
Section: Discussionsupporting
confidence: 55%
“…Applying this method, NA/NR complexes served as cargo and FLs as delivery vehicles. As already clearly shown for FLs in the absence of NR molecules and NAs [34,55], parallel experiments on NA/NR/FL complexes also proved fusion-based transfer and high biocompatibility [38]. Underlying liposomes (there named Fuse-It-mRNA) had the identical composition as characterized here as optimum (DOPE/DOTAP/DiR 1/1/0.1) and were unaffected in effectiveness by various endosomal uptake blockers while keeping natural cell functions of various cell types completely unaffected.…”
Section: Discussionsupporting
confidence: 55%
“…When CLs surf onto the surface of the cell membrane, cellular uptake may occur through endocytosis or membrane fusion ( Figure 3 ). In contrast, membrane fusion occurs almost exclusively in fusogenic CLs, 95 , 96 which directly translocate their cargo into the cytoplasm, 97 , 98 resulting in efficient drug delivery to the cytoplasm without endosomal entrapment and metabolic degradation. 99
Figure 3 Schematic Diagram of Lipoplexes Entering and Trafficking Within Cells: Entry Pathways and Intracellular Barriers Lipoplexes enter into cells via endocytosis or membrane fusion.
…”
Section: Main Textmentioning
confidence: 99%
“… 18 , 146 , 147 , 148 , 149 Kolašinac et al. 95 reported that an inverted conical shape and an aromatic molecule in cationic lipid are indispensable to the fusion induction. Bruininks et al.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in Chinese hamster ovary cells, Kolašinac et al showed that cationic fusogenic liposomes could reach a fusion efficiency ranging from 1 to 92% depending on the cationic lipid composition of the synthetic vesicles [ 52 ]. It is also illustrated that environmental conditions (ionic concentration, pH or buffer osmolality) impact the liposome fusion process which remains very low in physiological conditions [ 53 ]. Although this strategy has shown promise [ 54 ], lack of control over how the molecule is packaged into the vesicle and possible low entrapment of larger cargo may limit its wider applicability.…”
Section: Re-engineering Of the Parental Cellmentioning
confidence: 99%